Democratisation versus accountability - should the European Parliament be given more powers? - Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper challenges the assertion that European politics would be closer to the citizens preferences if decision power were transferred from the Council of Ministers to the European Parliament. On the one hand, citizens benefit from a greater transparency in the Parliaments debates compared to the Councils decisions. On the other hand, a powerful European Parliament would be less accountable to the voters of each state since in the European election each state is only decisive with a small probability.
Keywords: D72; H11; 330; Accountability; European institutions; transparency; democratisation; Europäische Integration; Parlament; Ökonomische Theorie der Demokratie; Public Choice; Unvollständiger Vertrag; Theorie